Serial innovators : - Feser, Claudio (Wiley, 2012)
This book studies the factors affecting the aging of firms, the factors that slow down the process of adapting to changes in the marketplace. It reviews the recent findings in relevant academic fields - behavioral economics, psychology, neuroscience, organizational science, network theory, anthropology, sociology, and strategy - to understand how firms, as they grow, develop rigidities that prevent change. It then uses those findings to develop a model of organization that is adaptive, innovative, and that can create significant value for its stakeholders for long periods, sometimes for centuries. Such a firm is driven by the passion to make a difference to customers and society; a firm that is led by learners with an ambitious and positive vision; a firm that is organized and that builds on its members' desire to achieve results, and their eagerness to grow and develop; a firm that is quick in developing new capabilities; a firm that, while it focuses thoroughly on execution and results, continuously challenges itself. The book also reflects on how- in building such firms - leaders can help people discover their true passions, build their self-confidence, develop their capabilities, and achieve great goals in their lives. It reflects on how leaders can be great leaders, on how leaders can build legacies. The book is an insightful page-turner. It combines the fictive, engaging story of a young and ambitious CEO who struggles to save his company from failure, with short, insightful and yet academically thorough reviews of recent developments in science relevant to company adaptation, innovation and growth.